A comparison of laws governing graveyards in Malaysia, Australia and England / Adlin Aimi Omar and Elfirra Thazali - Omar, Adlin Aimi; Thazali, Elfirra (2007)
Basically this study was initiated after realising that there is a need to know of the existence of laws relating to graveyards, the issues and problems due to the absence of specific legislations on graveyards. With a proposal which was submitted and approved by the lecturer of the subject of Legal Research and Methodology we began the research because it appeared to us that there may be a lack of space for burial grounds. However, further research was conducted and we realized that the most important matter is not the lack of space but the need to have a visible law regarding graveyards in Malaysia. This study will specifically look at the comparison of specific laws relating to graveyards and the issues that arise and how it may be solved. Through this study, it was found that in Malaysia there is no clear and precise laws relating to graveyards to act as a guideline to better administer all matters pertaining to it.